Three Essays on Real Estate Price Dynamics - António Manuel Pereira Rodrigues Cunha (2022)
This dissertation consists of three papers about real estate price determinants, house price dynamics, and the effects of tourism on house prices. The first paper corresponds to chapter 2, the second paper corresponds to chapter 3, and the third paper corresponds to chapter 4. The first paper investigates whether the previously identified real estate price determinants in the literature (gross domestic product, interest rates, construction cost, construction permits, and tourism) are the same in four different geographical levels of the same geopolitical space: the European Union (EU), 28 countries of the EU, one EU country (Portugal), and the Metropolitan Statistical Areas (MSA) of one country (Portugal 25 MSA). We applied two time series models and two panel data models to four samples of European data. We found that most of the previously found price determinants are statistically significant but have different impacts in each level of analysis. This finding has implications in terms of public policy and investment, suggesting that a 'one size fits all' approach is not appropriate for explaining real estate prices. In the second paper, we research the long-term house price equilibrium and the short-term house price dynamics (returns) at the MSA level, applying a two-step analysis to a sample with all Iberian (Spain and Portugal) MSA. In the first step, we modelled house prices according to the literature previously found determinants (gross domestic product, interest rates, and construction costs) and estimated the long-term equilibrium price under five different estimation models, comparing conventional panel methodologies with recent advances in econometrics. We found that, in the long run, the house price elasticity to income is much lower in Iberian MSA than what was found by previous studies in the United States of America (U.S.) MSA. In the second step, we used the long-term equilibrium price to estimate the error correction term of the short-term house price dynamics model, under another five different estimation models. In the short run, the macro fundamental factors that explain house price dynamics in the U.S. are not found to be statistically significant in Iberia. We found that there are significant differences in house price returns within Iberian MSA, and we hypothesize that there are other factors beyond previously found macro fundamentals that drive Iberian house prices in the short run, such as tourism. Finally, in the last paper, we study the effects of tourism short-term rentals in two Portuguese MSA (Lisbon and Porto) applying a difference-in-differences methodology. We innovate by testing a new econometric estimator in this quasi-experimental study and comparing the results with estimates obtained from conventional estimators. We show that the new estimator produces much higher and more precise estimates. We found that the liberalization of short-term rental licensing had a statistically significant impact on house prices, explaining the excess returns in the last decade's housing market. We found that the change of use from housing to tourism provoked a supply shock by reducing the housing supply of municipalities with inelastic supply. These results are important for local politicians and real estate investors. Policy decisions implemented to curb house price increases should address ways of increasing supply elasticity. Inversely, investors should look for markets where supply elasticity is expected to decrease. Collectively, our thesis contributes to the real estate finance literature by showing that real estate markets should be analysed locally, not globally, and that each market's elasticities (income and supply) are important factors in determining real estate price equilibrium and returns. We add to the literature on real estate price determinants and dynamics by studying the under-researched markets of Portugal and Spain. Moreover, we innovate by applying recent econometric advances that allow for slope heterogeneity and control for cross-sectional dependence in panel data estimations. We show that the literature previously found coefficients for house price elasticities to aggregate income that were biased and that the estimate of this elasticity is smaller than expected. We also innovate by applying a new econometric estimator to the difference-in-differences methodology, producing more precise estimates. We find that previous estimates of the effects of tourism on house prices using conventional econometric models were underestimating the impacts of short-term rentals in house prices. These contributions will help future real estate price investment researchers obtain unbiased and more precise estimates of real estate price determinants.